Nonlinear control of continuous cultures of Porphyridium purpureum in a photobioreactor. (17th February 2015) - Tebbani, Sihem; Lopes, Filipa; Becerra Celis, Giuliana
Abstract: Advanced control strategies proved to be promising tools to improve the performances of microalgae production systems, especially in the perspective of large scale cultivation plants. This paper proposes the validation of a nonlinear control strategy with experimental results. Additionally, the on-line estimation of the biomass concentration in a photobioreactor is presented. The proposed control law maintains the biomass concentration at a targeted level. This is achieved by a state feedback linearizing control law in an inner loop, in addition to a Proportional Integral regulator with an anti-windup compensation in an outer loop. To cope with the lack of on-line biomass concentration measurements, this variable is estimated on-line by an Extended Kalman Filter, based on available on-line measurements (pH, incident light intensity and dissolved carbon dioxide concentration). Performance and robustness of the proposed control strategy are assessed through experimental results obtained with cultures of the microalgae Porphyridium purpureum in a laboratory-scale continuous photobioreactor. Highlights: Experimental validation of a control strategy of a microalgae culture in a continuous photobioreactor with experimental data. Biomass concentration is regulated using a linearizing control law and a PI-controller. Anti-windup compensation is added to the PI-controller, improving closed-loop system performance. Biomass concentration is estimated with an Extended Kalman filter using available on-line measurements. The presented procedure can be applied to any microalgae species.